Antiglioma effects of N6‐isopentenyladenosine, an endogenous isoprenoid end product, through the downregulation of epidermal growth factor receptor. Issue 4 (16th November 2016) - Ciaglia, Elena; Abate, Mario; Laezza, Chiara; Pisanti, Simona; Vitale, Mario; Seneca, Vincenzo; Torelli, Giovanni; Franceschelli, Silvia; Catapano, Giuseppe; Gazzerro, Patrizia; Bifulco, Maurizio
Abstract : Malignant gliomas are highly dependent on the isoprenoid pathway for the synthesis of lipid moieties critical for cell proliferation. The isoprenoid derivative N6‐isopentenyladenosine (iPA) displays pleiotropic biological effects, including a direct anti‐tumor activity in several tumor models. The antiglioma effects of iPA was then explored in U87MG cells both in vitro and grafted in mice and the related molecular mechanism confirmed in primary derived patients' glioma cells. iPA powerfully inhibited tumor cell growth and induced caspase‐dependent apoptosis through a mechanism involving a marked accumulation of the pro‐apoptotic BIM protein and inhibition of EGFR. Indeed, activating AMPK following conversion into its iPAMP active form, iPA stimulated EGFR phosphorylation and ubiquitination along a proteasome‐mediated pathway which was responsible for receptor degradation and its downstream signaling pathways inhibition, including the STAT3, ERK and AKT cascade. The inhibition of AMPK by compound C prevented iPA‐mediated phosphorylation of EGFR, known to precede receptor loss. As expected the block of EGFR degradation, by exposure to the proteasome inhibitor MG132, significantly reduced iPA‐induced cell death. Given the importance of receptor degradation in iPA‐mediated cytotoxicity, we also documented that the EGFR expression levels in a panel of primary glioma cells confers them a high sensitivity to iPA treatment. In conclusion our study provides the first evidence of iPA antiglioma effect. Indeed, as glioma is driven by aberrant signaling of growth factor receptors, particularly the EGFR, iPA, alone or in association with EGFR targeted therapies, might be a promising therapeutic tool to achieve a potent anti‐tumoral effect. Abstract : What's new? A modest efficacy is achieved by treatment strategies targeting the aberrant signaling from EGFR in glioma, validating EGFR as a therapeutic target but motivating the development of improved anti‐EGFR strategies. The isoprenoid pathway, frequently deregulated, is a promising target: as EGFR is highly dependent on the isoprenoid moieties for correct localization and signaling, its manipulation by isoprenoid‐derivatives offers a new valid opportunity. Here, the authors report for the first time the antitumor activity of the isoprenoid derivative N6‐isopentenyladenosine (iPA) on glioma cells and its action mechanism mediated primarily through AMPK‐dependent EGFR degradation, by which cell growth and survival are affected.